Western Centric Medicine for Covid-19 and Its Contradictions: Can African Alternate Solutions Be the Cure? - Adunimay, Anslem Wongibeh; Ojo, Tinuade A. (Frontiers in Political Science, 2022)
The full impact of covid-19 is yet to be fully understood, and while there are many unknowns, the rapid and continued reliance on the internet cannot be denied. Some Global Economy and World Health Organizations have discouraged the usage of traditional medicine for Covid-19 treatment. However, some African states such as Tanzania, Equatorial Guinea, Guinea-Bissau, Guinea Conakry and Togo have engaged with formal researchers to see if traditional medicine can treat covid-19. Nevertheless, there is still a lot of hesitancy amongst African populations in getting vaccinated. The paper conceptualizes the criticism of Western-centric medicine and investigates the promotion of alternate approaches in the African economy. The article situates the study context by exploring the African economy’s socio-politics and public health governance. It investigates explicitly African states responses to conventional treatment by analyzing the role of traditional medicine, how effective the efficacy is, and the possible effects on the continent. Finally, the paper will employ secondary data to present a detailed literature analysis to evaluate current traditional medicine’s impact and future treatment of covid-19.